Advanced cardiovascular life support : ACLS course and ACLS renewal course/ instructor CD (American Heart Association, 2016)
This program provides information to ACLS providers, expert clinicians and scientists on advanced resuscitation procedures. It demonstrates how to assess and manage critical cardiovascular emergencies not currently addressed in ACLS. It may also be used as adult continuing education for learners who wish to improve their knowledge and skills in ACLS but are not required to document successful completion of the ACLS-EP course.